Economic cost of smoking in people with mental disorders in the UK - Wu, Qi; Szatkowski, Lisa; Britton, John; Parrott, Steve (BMJ Publishing Group, 2015)
Background Smoking is the largest preventable cause of death in the UK and imposes a huge economic burden on society. Both the prevalence and extent of smoking are significantly higher among people with mental disorders than among the general population.